2-(2-Fluoro-4-hydroxybenzyl)isoindoline-1,3-dione - Vesek, Hilal; Kazak, Canan; Agar, Aysen Alaman; Gumus, Sumeyye; Aygun, Muhittin (Int Union Crystallography, 2012)
In the title compound, C15H10FNO3, the dihedral angle between the isoindoline-1,3-dione and 3-fluoro-4-methyl-phenol groups is 86.88 (8)degrees. The isoindoline-1,3-dione fragment is almost planar, with an r.m.s. deviation of 0.0154 A within the group. Intermolecular C-H center dot center dot center dot O hydrogen bonds generate C(6) chains running parallel to the [010] direction.
Aygün, Muhittin/0000-0001-9670-9062;